Mechanical properties of thermoformed multilayer parts containing non thermoformable materials - Wittmann, Lisa-Maria; Drummer, Dietmar (Journal of Plastic Film & Sheeting, 2022)
Different viscous materials were chosen to simulate the behavior of degraded materials in the thermoforming process and to demonstrate the potential of using multilayer sheets for thermoforming non thermoformable materials without losing final part performance. The mechanical properties of thermoformed multilayer sheets with 3, 22, and 50 melt flow index (MFI) polypropylenes (PP) were investigated. Therefore, a thermoformable material (MFI-3) and difficult/non thermoformable (MFI-22 and MFI-50) material was combined in the bilayer sheet. The extruded bilayer sheets had equal layer thicknesses (A/B 50%/50%) and unequal layer thicknesses (A/B 70%/30%), whereby B is always the material difficult to thermoform. As the non thermoformable material can lead to inhomogenity in the wall thickness and therefore can cause different part performance, the investigation focused on how the non thermoformable material influenced the mechanical performance of the final part. This labortory scale thermoformability investigation of the extruded PP sheets with different viscosities showed that the low viscous layer position has only a marginal influence on the general mechanical properties of the thermoformed parts. The mechanical properties can be predicted more precisely by the mechanical properties of the thermoformable material used than by the rule of mixtures. Whereas the Young’s modulus and yield stress change only negligibly, the elongation at break after thermoforming significantly increases with the stable component.<br
Keywords: Thermoformability; multilayer sheets; mechanical properties; wall thickness; less viscous materials